Kategori Pejalan Kaki di Jalur Pedestrian: Kriteria dan Konsep Perancangan - Salma Nur Afifah; Annisa Safira Riska; Hanson E. Kusuma (Jurusan Seni Rupa ISBI Bandung, 2025)
Walking is a physical activity that is useful for improving public health. Indonesia is still a country with a low ranking in terms of walking. To improve the walking program, it requires the cooperation of the community, government, and planners as providers of great and comfortable walking paths. In the pedestrian path design process, it is necessary to study the criteria for a great path in terms of user activity. The purpose of this study is to determine the characteristics of pedestrians in terms of the relationship between the reasons for walking and the activities carried out on the pedestrian path. This research uses qualitative methods with a grounded theory approach. Data collection was carried out by using online questionnaire. The results showed that the characteristics of pedestrians on the pedestrian path were divided into four groups, namely connoisseurs, recreation, consumptive, and functional. The dominant group is found by the group of connoisseurs related to the quality of the pedestrian path so it can be concluded that the quality of the pedestrian path is affects people to walk. This study also found partners walking on pedestrians dominated by friends.